PENGARUH SENAM LANSIA TERHADAP DEPRESI PADA LANSIA DI POSYANDU LANSIA BANJAR BINA KELURAHAN USADA - Ni Nyoman Purnaningsih; I Putu Artha Wijaya; IGAA Sherlyna Prihandhani; I Made Dwie Pradnya Susila (Jurnal Ilmiah Keperawatan, 2024)
Background: The older one is, the more likely a person experiences physical, physiological, mental, spiritual, economic and social problems. Depression is among the mental health issues that older people experience the most frequently. Depression in the elderly is usually caused by the loss of loved ones, physical functions, and inability to adapt. There are various types of therapy for depression, for example drug and physical therapy, one of which is exercise. Objective: To determine the level of depression before and after elderly exercise and the effect of elderly exercise on depression. Method: This research used a pre-experimental research method using a one-group pretest-posttest design. The reachable population in this study were 31 elderly at Posyandu Banjar Bina Kelurahan Usada. In accordance with the sample size formula, the researcher took 24 elderly as samples using purposive sampling based on the predetermined inclusion and exclusion criteria. The required data was collected using the GDS (Geriatric Depression Scale) questionnaire issued by the Ministry of Health of the Republic of Indonesia. Results: Based on their the level of depression, the mean score before the exercise for the elderly was a figure of 5.71 (moderate depression) whereas after the elderly exercise, the level of depression mean score decreased 2.88 (normal). The results of the Wilcoxon Signed Rank Test also showed that the significance value (p-value) was 0.000 < 0.05; therefore, H0 was rejected and Ha was accepted. Conclusion: There was an effect of implementing elderly exercise on reducing the level of depression in the elderly at Posyandu Lansia Banjar Bina Kelurahan Usada.